Unheard Voices: Navigating Sexual Harassment and Victim-Blaming at Mohammed First University - Taha, Hajar; Elyousfi, Redouane (Integrated Journal for Research in Arts and Humanities, 2024)
Sexual assault in universities has dominated recent headlines, as students across the country are coming together to speak out against a culture of sexual violence many feel is pervading their campuses. However, nobody is aware of exactly how pervasive the sexual demands are in Moroccan universities as victims fail to report the harassment over fears of social shaming. Female students are often hesitant to report sexual harassment and frequently face victim-blaming attitudes, particularly from men in positions of authority. Therefore, this paper aims to elucidate the key theories that interlink to form a pervasive culture of woman-blaming, which contributes to the prevalence of moral decadence. While women are undoubtedly blamed due to sexism and misogyny, this phenomenon is further reinforced by additional factors, such as rape myths and stereotypes, belief in a just world, individualism and collectivism, attribution bias, self-preservation instincts, denial of personal vulnerability, and counterfactual thinking. Moreover, this paper assesses attitudinal constructs hypothesized to be related to victim-blaming as part of a survey on UMP students to examine the reasons why some people tend to blame victims of sexual harassment and how this denial significantly contributes to the promotion of misogyny and sexism.